Georgios Deligiannakis. The Dodecanese and the Eastern Aegean Islands in Late Antiquity, AD 300–700. - Roussos, Konstantinos (Journal of Greek Archaeology, 2019)
This substantial book derives from Deligiannakis’ doctoral thesis, and for this reason it is bibliographically updated until 2006, although it has been published 10 years later in 2016. It focuses on a particular chronological period – Late Antiquity (300–700) – during which insular communities played a major role on multiple levels. Despite the fact that it places a particular focus on the Dodecanese and the Eastern Aegean Islands, the author adopts a broader geographical perspective, using comparative material from both island (Crete, Cyprus, Cyclades etc.) and mainland regions (Asia Minor, Greek mainland etc.).